El marxismo y la liberación homosexual Las relaciones de Magnus Hirschfeld con el Partido Socialdemócrata de Alemania y con el primer gobierno soviético - Gaido, Daniel (Ariadna Ediciones, 2023)
The annulment and reimposition of the "crime of sodomy" and the creation of the first homosexual liberation movement. Magnus Hirschfeld's collaboration with the Social Democratic Party of Germany for the decriminalization of homosexuality. Homosexual liberation and women's liberation in the Social Democratic Party and the Communist Party of Germany. The decriminalization of homosexuality in Soviet Russia and the laws against minor prostitution in Transcaucasia and Central Asia. The persecution of Magnus Hirschfeld by the Nazis and the recriminalization of homosexuality in the Soviet Union by Stalin.